Evaluation of Production Capability of Transportation Equipment and Loading Equipment in Limestone Mining at PT X, South Sulawesi - Aditya, Muhammad Tri; Arystianto, Deni Putra; Jayaputra, Harsalim Aimunandar; Susilo, Helik; Pratama, Gindang Rain (Westscience Press, 2024)
This study focuses on the evaluation of the production capacity of loading and hauling equipment in limestone mining operations at PT. X, South Sulawesi Province. The selection of this topic is based on the importance of operational efficiency in limestone mining which has a direct impact on the productivity and sustainability of the cement industry. The main objectives of this study are to determine the actual production of loading and hauling equipment, determine the number of equipment needed to meet production targets and identify compatibility factors between mechanical equipment at the mining site. The methods used include field data collection involving measurement of cycle time and production capacity of loading and hauling equipment. The data obtained are then processed using statistical methods to ensure the accuracy of the results. Data analysis is carried out by considering variables such as work efficiency, cycle time, and equipment capacity. The results show that Kobelco SK 480 LC has the highest production capacity (509.34 tons/hour), followed by Komatsu PC 400 (448.25 tons/hour) and PC 300 (417.05 tons/hour). To achieve the Crusher production target of 1450 tons/hour, a combination of loading equipment and dump trucks with a compatibility factor between 0.87 and 0.92 is required, indicating potential for increased efficiency. It is recommended to improve maintenance of equipment and mining roads to optimize productivity.